Influence of main chain on the phase behaviors of side‐chain liquid‐crystalline polymers with triphenylene mesogens of long alkyl tail substituents. Issue 4 (30th November 2016) - Li, Ping; Chen, Sheng; Luo, Hang; Zhang, Dou; Zhang, Hailiang
ABSTRACT: A series of side‐chain liquid‐crystalline polymers (SCLCPs) containing triphenylene mesogen, in which the long alkyl tail Tp connected directly with main chain, were synthesized successfully. The chemical structures of the monomers were confirmed by 1 H NMR and mass spectrometry. The phase behaviors of polymers were investigated by a combination of techniques, including DSC, POM, 1D/2D WAXD, and SAXS. The experimental results suggested that the type of main chain played an important role in the LC phase structures of these polymers. Because of the steric effects of side chains and the coupling effects between the Tp moieties and the main chains, all the polymers exhibited columnar phase. However, the SCLCPs with poly(vinyl benzene methyl ether) or polynorbornene backbone displayed hexagonal columnar phase, while those with polyacrylate or polymethacrylate backbone presented columnar nematic phase, and the one with poly(vinyl benzoate) main chain showed rectangular columnar phase. Moreover, the clearing temperatures (Ti) changed with change in main chain. Especially, the Ti of the SCLCP with polymethacrylate backbone was above 300 °C. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 754–766 Abstract : This article describes the successful synthesis of a series of side‐chain liquid‐crystalline polymers, containing long alkyl chain triphenylene mesogens. The effects of the main chain on the phase behaviors and phase structures of the polymers have been studied. The results indicate the presence of columnar structure for all the polymers, consisting of the main chain and Tp moieties, which were independent of the main chain. However, the clearing temperatures are strongly dependent on the main chain.